Destabilization of β cell FIT2 by saturated fatty acids alter lipid droplet numbers and contribute to ER stress and diabetes - Zheng, Xiaofeng (2022)
SignificanceWith obesity on the rise, there is a growing appreciation for intracellular lipid droplet (LD) regulation. Here, we show how saturated fatty acids (SFAs) reduce fat storage-inducing transmembrane protein 2 (FIT2)-facilitated, pancreatic β cell LD biogenesis, which in turn induces β cell dysfunction and death, leading to diabetes. This mechanism involves direct acylation of FIT2 cysteine residues, which then marks the FIT2 protein for endoplasmic reticulum (ER)-associated degradation. Loss of β cell FIT2 and LDs reduces insulin secretion, increases intracellular ceramides, stimulates ER stress, and exacerbates diet-induced diabetes in mice. While palmitate and stearate degrade FIT2, unsaturated fatty acids such as palmitoleate and oleate do not, results of which extend to nutrition and diabetes.